Cerita Rakyat Asal Mula Situ Patenggang: Analisis Naratologi Vladimir Propp - Nugraha, Cheryll Adinda; Nama, I Ketut; Putra, Jalu Norva Illa (CV. Eduartpia Publisher, 2025)
This article aims to examine and describe the narratological aspects in the folktale book Asal Mula Situ Patenggang. This study uses a structural theory based on Vladimir Propp's narratology. The research method used is descriptive analytic driven by structural theory by using reading, listening, and note-taking techniques. The results of this analysis are the analysis of the narrative structure in the folktale book Asal Mula Situ Patenggang written by Asep Setiawan and U. Syahbudin. The analysis of the narrative structure shows that Propp's narratological aspect has three stages, namely the function of the actor, the story pattern, and the distribution of functions among the actors. The results of the analysis focus on when the folktale begins, namely from the title of the story part 2 to 11. The hero in this story is Eyang Jagasatru. The supporting actors are several characters who have roles as donors, helpers, intermediaries, and false heroes. From these three stages, thirteen actor functions, three story patterns with five circles of action were found. However, nineteen functions do not appear in the story because the absence of the functions proposed by Propp is contextual and not universal